Competence-based teacher education programmes: Transitioning towards a paradigm shift or preserving the traditional? - Fjolla Kacaniku (Universidad de Deusto, 2024)
Adapting teacher education programs to societal changes is a current issue, especially when viewed through the European frameworks driving transformative reforms. The paper reports how European frameworks and other initiatives in higher education and teacher education aim to support the transformation of teacher education programmes. Multiple European-level interventions have engendered shifts in the conceptual understanding and orientation of initial teacher education programmes across numerous contexts within Europe. The purpose of this paper was to examine the shift of teacher education programmes into competence-based in Kosovo, the youngest country in Europe, in the context of European frameworks as an impetus for transition. This qualitative research is a part of a broader study that involves analysing study programmes, conducting interviews with teacher educators and management staff, and holding focus groups with student-teachers. The goal is to explore the path of contextualizing European-inspired programme reforms in more detail. The findings show that Kosovo is shifting to a competence-based approach to align with EU integration, incorporating European principles for programme improvement. However, the study reveals a notable focus on maintaining programmes' tradition. This leads to tensions and contradictions regarding programme tradition, EU integration goals, and actual implementation. The results provide valuable insights into the significance of educational context and the tacit knowledge of teacher educators and other stakeholders during programme reforms within the context of European initiatives. Received: 29 April 2023 Accepted: 13 January 2024